A study on the satisfaction of employees’ working relationships at the Ministry of Defence, Kuala Lumpur - Muhammad Syafiq, Othman (2021)
Working satisfaction is one of the most important topics that need to be addressed. Currently, the increasing number of young employees in the workforce is attracting more benefits for the organizations. With the new era of workforce involving different demographic backgrounds, working in a team could lead to lower satisfaction in the workplace. The main purpose of this study is to investigate the perception of working relationships with older employees in terms of communicative teamwork, mutual learning, and communicating feedback towards working satisfaction among young employees at The Ministry of Defence, Kuala Lumpur. The population of this study was limited to 175 young employees of age 40 and below. Communication Accommodation Theory (CAT) was used in this study. The theory postulated that communicators from different social groups may influence interpersonal communication. The finding from this study indicated that young employees have a positive working relationship with older employees. They learned a lot from the older employees at the same time received positive feedback from the older employees. The findings can help both young and older employees to have a better understanding and improved relationship at the workplace.